Tumor-Targeting Glycol Chitosan Nanoparticles for Image-Guided Surgery of Rabbit Orthotopic VX2 Lung Cancer - On, Kyeong Cheol; Rho, Jiyun; Yoon, Hong Yeol; Chang, Hyeyoun; Yhee, Ji Young; Yoon, Jun Sik; Jeong, Seo Young; Kim, Hyun Koo; Kim, Kwangmeyung (MDPI, 2020)
Theranostic nanoparticles can deliver therapeutic agents as well as diverse imaging agents to tumors. The enhanced permeation and retention (EPR) effect is regarded as a crucial mechanism for the tumor-targeted delivery of nanoparticles. Although a large number of studies of the EPR effect of theranostic nanoparticles have been performed, the effect of the change in the body size of the host on the EPR effect is not fully understood. In this regard, comparative research is needed on the behavior of nanoparticles in large animals for developing the nanoparticles to the clinical stage. In this study, we prepared fluorophore (indocyanine green (ICG) or cyanine 5.5 (Cy5.5))-conjugated glycol chitosan nanoparticles (CNPs) for comparing the tumor-targeting efficacy in VX2 tumor-bearing mouse and rabbit models. As expected, the CNPs formed nano-sized spherical nanoparticles and were stable for 8 days under aqueous conditions. The CNPs also exhibited dose-dependent cellular uptake into VX2 tumor cells without cytotoxicity. The half-life of the near-infrared fluorescence (NIRF) signals in the blood were 3.25 h and 4.73 h when the CNPs were injected into mice and rabbits, respectively. Importantly, the CNPs showed excellent tumor accumulation and prolonged biodistribution profiles in both the VX2 tumor-bearing mouse and rabbit models, wherein the tumor accumulation was maximized at 48 h and 72 h, respectively. Based on the excellent tumor accumulation of the CNPs, finally, the CNPs were used in the image-guided surgery of the rabbit orthotopic VX2 lung tumor model. The lung tumor tissue was successfully removed based on the NIRF signal from the CNPs in the tumor tissue. This study shows that CNPs can be potentially used for tumor theragnosis in small animals and large animals.
Keywords: FLUORESCENCE; DELIVERY; VISUALIZATION; CHEMISTRY; DESIGN; SYSTEM; LIGHT